2011
DOI: 10.1161/circresaha.111.243444
|View full text |Cite
|
Sign up to set email alerts
|

Ets2 Determines the Inflammatory State of Endothelial Cells in Advanced Atherosclerotic Lesions

Abstract: Rationale: Neovascularization is required for embryonic development and plays a central role in diseases in adults. In atherosclerosis, the role of neovascularization remains to be elucidated. In a genome-wide microarrayscreen of Flk1؉ angioblasts during murine embryogenesis, the v-ets erythroblastosis virus E26 oncogene homolog 2 (Ets2) transcription factor was identified as a potential angiogenic factor. Objectives:We assessed the role of Ets2 in endothelial cells during atherosclerotic lesion progression to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 36 publications
4
32
1
Order By: Relevance
“…Interestingly, VCAM-1 expression is regulated in a Rac1-dependent fashion, whereas ICAM-1 is not (Ahmad et al, 2002;Ng et al, 2002;Marinkovic et al, 2014b). This exclusiveness of VCAM-1 regulation has also been observed with transcription factor Ets-2 in endothelial cells (Cheng et al, 2011), although Rac1 involvement has not been determined here.…”
Section: Role Of Rac1 In the Vasculature Endothelial Cellssupporting
confidence: 68%
“…Interestingly, VCAM-1 expression is regulated in a Rac1-dependent fashion, whereas ICAM-1 is not (Ahmad et al, 2002;Ng et al, 2002;Marinkovic et al, 2014b). This exclusiveness of VCAM-1 regulation has also been observed with transcription factor Ets-2 in endothelial cells (Cheng et al, 2011), although Rac1 involvement has not been determined here.…”
Section: Role Of Rac1 In the Vasculature Endothelial Cellssupporting
confidence: 68%
“…Protein bands were visualized with the Li-Cor detection system (Westburg, Leusden, the Netherlands) as previously described. [15][16][17] …”
Section: Qpcr and Western Blot Analysismentioning
confidence: 99%
“…Recently, Cheng and colleagues showed that the transcription factor Ets-2 translocates to the nucleus upon TNF-α treatment and regulates VCAM-1 mRNA expression (Cheng et al, 2011). Our data showed that in Trio-deficient cells, TNF-α-induced Ets-2 translocation to the nucleus is prevented (Fig.…”
Section: Resultsmentioning
confidence: 99%